Cough in Children: Clinical Approach - Banu Gülcan Öksüz (Güncel Pediatri, 2015)
Cough is an important reflex defense mechanism and it cleans the airways with the various stimuli. Children are more sensitive than adults to these environmental stimuli. Full mechanism of the cough reflex have not been completely analyzed. Causes of chronic cough in children are different from adults. Even cough is normal for most children, the presence of cough may be indicative of serious disorders and should be considered important because cough affects the child’s quality of life. All children with chronic cough should be evaluated for diagnosis. Cough in children should be treated based on etiology. There is no evidence of the affect of symptomatic treatment for cough in children.